Nitrogen‐Doped Nanocarbons Derived from Tetrazine Cross‐Linked Poly(4‐cyanostyrene)‐Silica Hybrids. Issue 18 (24th January 2017) - Lamson, Melissa; Chen, Luyi; Zhong, Mingjiang; Wu, Dingcai; Matyjaszewski, Krzysztof
Abstract : Novel nanoporous carbon materials with nitrogen‐doping and high porosity are successfully developed by utilizing well‐defined hairy poly(4‐cyanostyrene) grafted silica nanoparticles as building blocks. The hairy nanoparticles are cross‐linked via the Pinner reaction to form tetrazine cross‐linking units. Subsequent carbonization and silica etching yield the 3D‐interconnected nitrogen‐doped nanocarbon networks with surface areas exceeding 750 m 2 g −1 . Abstract : Nanoporous carbon materials containing heteroatoms are important for various applications. Novel carbon precursors containing cyano groups are grafted from silica particles by surface‐initiated atom transfer radical polymerization of 4‐cyanostyrene. The poly(4‐cyanostyrene) grafted silica particles are cross‐linked via the Pinner reaction to form tetrazine cross‐linking units. The cross‐linked nanoparticles exhibit intra‐ and interparticle cross‐linking, as confirmed by dynamic light scattering and scanning electron microscope analysis. Subsequent carbonization and silica etching yield a 3D‐interconnected network of nitrogen‐doped nanocarbons with surface areas exceeding 750 m 2 g −1 .